Rightward collisions and their association with pseudoneglect - Nicholls, M.; Loftus, Andrea; Orr, C.; Barre, N. (Academic Press, 2008)
Whereas right parietal damage can result in left hemineglect, the general population shows a subtleneglect of the right hemispace—known as pseudoneglect. A recent study has demonstrated that peoplecollide to the right more often and attributed this bias to pseudoneglect. [Nicholls, M. E. R., Loftus, A.,Meyer, K., & Mattingley, J.B. (2007). Things that go bump in the right: The effect of unimanual activityon rightward collisions. Neuropsychologia, 45, 1122–1126]. Nicholls examined the effect of unimanualactivation by requiring participants to fire projectiles at a target whilst walking and found that the rightward bias was exaggerated or reversed when the left and right hands were active, respectively. However, the act of aiming at a target may have inadvertently biased walking trajectory to the right. The current study addressed this issue by requiring participants (n = 149) to walk through a narrow doorway three times whilst entering text into a phone using the (a) left, (b) right or (c) both hands. Despite the fact that entering text into a phone should produce no rightward bias, participants bumped to the right more often. Unlike previous research, no effect of unimanual activation was observed. This lack of effect was attributed to the smaller hand movements for entering numbers compared to firing a toy gun. Finally, this study showed an association for the first time between biases in observable bumping and line bisection performance—suggesting that unilateral bumping is related to pseudoneglect.